1996
DOI: 10.1038/nbt1196-1557
|View full text |Cite
|
Sign up to set email alerts
|

The extreme sensitivity of Mycobacterium tuberculosis to the front-line antituberculosis drug isoniazid

Abstract: Mycobacterium tuberculosis is a natural mutant in oxyR, a close homolog of the central regulator of peroxide stress response in enteric bacteria. Inactivation of oxyR is specific for M. tuberculosis and other members of the M. tuberculosis complex. This phenomenon appears as a paradox due to the ability of this organism to parasitize host macrophages, in which the ingested organisms are likely to be exposed to reactive oxygen intermediates. However, the surprising finding that M. tuberculosis has multiple dele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 52 publications
0
43
0
2
Order By: Relevance
“…However, until recently, the mechanism of INH activity remained unclear. Field strains of M. tuberculosis were found to naturally contain mutations in oxyR, a gene encoding a key regulator of the peroxide stress response, which may account for the exceptionally high sensitivity of M. tuberculosis to INH (62). Studies conducted over the last decade have led to the isolation and characterization of the molecular target of INH in mycobacteria (44).…”
Section: Discussionmentioning
confidence: 99%
“…However, until recently, the mechanism of INH activity remained unclear. Field strains of M. tuberculosis were found to naturally contain mutations in oxyR, a gene encoding a key regulator of the peroxide stress response, which may account for the exceptionally high sensitivity of M. tuberculosis to INH (62). Studies conducted over the last decade have led to the isolation and characterization of the molecular target of INH in mycobacteria (44).…”
Section: Discussionmentioning
confidence: 99%
“…With NAD ϩ included in the mix, the generation of the isonicotinoyl-NAD adduct was observed both with and without KatG present (7)(8)(9), leading to the suggestions that the role of KatG is limited to the hydrazinolysis of INH and that the subsequent reaction of the isonicotinoyl radical with NAD ϩ is a nonenzymatic event involving a homolytic aromatic substitution (7,10). Reactive oxygen species have been implicated in INH activation both in vivo (11,12) and in vitro (6), and an elevated level of superoxide (13) was identified as a possible reason for the high sensitivity of M. tuberculosis to INH (1). However, the absence of H 2 O 2 involvement in INH activation implies that a reaction different from either the peroxidase or the catalase reactions is involved, and some reports have suggested that the active participation of KatG in INH activation involves more than just hydrazinolysis (9).…”
Section: Isonicotinic Acid Hydrazide (Isoniazid or Inh)mentioning
confidence: 99%
“…This environment includes peroxides formed by the oxidative burst, species such as peroxynitrite formed by the inducible nitric oxide synthase, and the alkyl peroxides that result from exposure of unsaturated lipids to oxidative stress. Analysis of the genes induced in isoniazid-resistant M. tuberculosis indicates that one of the mechanisms used by the organism to compensate for loss of the KatG antioxidant activity is to up-regulate the ahpC gene product, which codes for a non-hemoprotein alkylhydroperoxidase (15)(16)(17)(18)(19). Incubation of M. tuberculosis expressing elevated levels of the alkylhydroperoxidase with isoniazid has shown that the drug is not activated by this enzyme (15).…”
mentioning
confidence: 99%